Potret Kesedihan Tokoh dalam novel Gerhana Kembar karya Clara NG - Mardhatillah, Rizka; Adek, Muhammad (Universitas Negeri Padang, 2024)
This study aims to describe the portrait of sadness experienced by the main character in the novel Gerhana Kembar by Clara Ng. The type of research used is literary research with descriptive method. The methodological approach used in this research is literary psychology, with the theoretical framework of the Five Stages of Grief from Kübler-Ross (1969). The data source in this research is the novel Gerhana Kembar by Clara Ng published in 2015 by Gramedia Pustaka Utama. The data collection technique consists of intensive reading and understanding the contents of the novel carefully and meticulously to gain an understanding of the novel, marking the characters' speech and narration in the novel that is in accordance with the research problem, inventorying the required data contained in the novel. Data analysis techniques in this study are classifying data, analyzing data and connecting with theory and providing critical views, drawing conclusions from the analyzed data. The results of the analysis show that the stages of the main character's grief include the five stages of denial, anger, bargaining, depression and acceptance caused by the loss of valuable things, separation, changes in atmosphere and environment, conflicts in relationships and provide psychological impact and physical impact.